Knowledge of glaucoma among patients of selected health facilities in Ondo state, Nigeria - Fasoranti, Abimbola B.; Fasoranti, Ifedayo O.; Onwuama, Mercy; Kareem, Abiodun J. (International Journal Of Community Medicine And Public Health, 2023)
Background: Glaucoma is the leading cause of irreversible blindness globally hence, the need for individual to acquire knowledge of prevention, control and appropriate management. This study sought to assess the knowledge of glaucoma among patients of selected health facilities in Ondo state, Nigeria. Methods: This research was a descriptive study. A total of 366 respondents selected randomly from the two health facilities in Ondo-state participated in the research. A self-structured questionnaire was used in collecting relevant data. Data were analyzed and level of significant was at p value 0.05. Results: Out of a total of 366 respondents, females 216 (59%) dominate, the majority were aged between 21-30 years (20.8%). Above half (51.1%) had tertiary level of education. Participants’ awareness (64.8%) and knowledge (49.7%) of glaucoma was good. Socio-demographic profiles had no relationship with level of knowledge of glaucoma. Conclusions: The awareness and knowledge about glaucoma was fairly good among the patients in Ondo state. The study findings stress the need to enhance awareness and knowledge through public oriented glaucoma education. Also, appropriate patient education and planning might positively affect the patients’ adherence to glaucoma medications.